Our iceberg is melting [changing and succeeding under any conditions] - Kotter, John P., 1947-; Rathgeber, Holger; Wyman, Oliver; Johnson, Spencer (New York : Audio Renaissance Audiobook : Distributed by Holtzbrinck Publishers, 2006)
One penguin finds a problem that could become a big problem for the whole colony. However, none of the other penguins want to listen.
Subtitle from container.
Unabridged.
Compact discs.
In container (17 cm.)
"Bonus CD: An original discussion with John Kotter and Holger Rathgeber on creative ways to put the lessons from Our Iceberg is Melting into practice"--Container.
Read by Oliver Wyman.
Keywords: Audiobooks; Organizational change; Organizational effectiveness; Penguins -- Fiction